2017
DOI: 10.1111/eci.12802
|View full text |Cite
|
Sign up to set email alerts
|

Lean body mass and creatine kinase are associated with reduced inflammation in obesity

Abstract: Inflammatory parameters were related to reduced lean mass and CK in an overweight and obese population. Hypothetically, lean mass has a favourable effect on obesity-related inflammation, and CK may play a role as an inhibitor of inflammation in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…This result parallels the finding in a previous clinical study comparing CK and CRP in obese individuals [ 1 ]. In that study, which motivated the present one, CK and lean body mass were negatively associated with CRP indicating an inhibitory effect on obesity-related inflammation by CK and/or by other muscular metabolites [ 1 ]. The present study therefore supports an inverse relationship between CK and CRP by its presence in the general population, but an influence of obesity is not confirmed from these data.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result parallels the finding in a previous clinical study comparing CK and CRP in obese individuals [ 1 ]. In that study, which motivated the present one, CK and lean body mass were negatively associated with CRP indicating an inhibitory effect on obesity-related inflammation by CK and/or by other muscular metabolites [ 1 ]. The present study therefore supports an inverse relationship between CK and CRP by its presence in the general population, but an influence of obesity is not confirmed from these data.…”
Section: Discussionsupporting
confidence: 91%
“…Creatine kinase (CK), an enzyme promoting cellular energy metabolism mainly in skeletal muscles, has been associated with inflammation. Mechanisms to explain this are not established, but obesity is a possible link [ 1 ]. Plasma levels of inflammatory biomarkers predict obesity [ 2 4 ], and obesity-related inflammation is associated with increased risk of cardiovascular diseases (CVD) and CVD-mortality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies show that plasma CK levels are associated with decreased inflammation in obesity, whereas higher inflammation is associated with higher obesity-related cardiovascular disease (CVD) [5][6][7]. Another study reported that plasma CK levels were inversely and independently associated with C-reactive protein in 454 overweight and obese individuals, supporting the anti-inflammatory effects of plasma CK levels [8]. Thus, plasma CK may have beneficial and detrimental effects on prognosis in the general population.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, plasma CK is associated with decreased inflammation in obesity, whereas higher inflammation is associated with higher obesity-related cardiovascular disease (CVD) [5][6][7]. Besides, CK and lean body mass were inversely and independently associated with C-reactive protein in 454 overweight and obese individuals, supporting the anti-inflammatory effects of plasma CK [8]. Thus, plasma CK may have beneficial and detrimental effects on prognosis in the general population.…”
Section: Introductionmentioning
confidence: 99%